Quality of nursing care : perception of parents of newborns hospitalized in neonatal units (2018)
ABSTRACT: Objective. This work sought to describe the quality of nursing care from the perceptions of parents of children hospitalized in a neonatal unit. Methods. Descriptive cross-sectional study conducted in an institution with tier III level of care in the city of Medellín (Colombia). Information was gathered by using the CARE-Q instrument, which was answered by the parents of newborns hospitalized in neonatal unit. The sampling was intentional. Results. The study had the participation of 121 individuals; 67.8% were women; mean age was 28 years and almost one in every two had secondary education or higher. Among the neonates, 66.9% were premature and 33.1% were to term, average weight was 2015 g (minimum 620 and maximum 4420). The general assessment of the parents on the quality of nursing care their children received in the neonatal unit, was on average 88 of 100 possible points. The scores obtained in the dimensions from highest tolowest were: Monitors and follows through (95.2), Accessibility (90.8), Maintains a relationship of trust (88.6), Comforts (87.2), Explains and facilitates (86.3), and Anticipates (86.0). Conclusion. Parents perceive as positive the nursing care their children receive in the neonatal unit. However, in the analysis by dimensions, it is possible to establish the need to strengthen aspects, like interpersonal relations and communication processes, which are part of the dimensions: Explains and facilitates and Anticipates. The findings permit guiding specific actions to improve quality in neonatal care.